Skrining Glukosa Darah Pada Masyarakat di Sekitar Gelanggan Olahraga Kadrie Oening Samarinda - Aminuddin, Muhammad Fahmi; Kamil; Rampo, Herniaty (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2023)
Diabetes mellitus (DM) is a non-communicable disease that is the center of attention for the world, including Indonesia. The increase in DM sufferers in Indonesia has occurred in the last few decades. DM can strike any age. Most DM disease is in the form of type 2 DM which is caused by the influence of food patterns, while very little type 1 DM is caused by genetic factors. The purpose of this community service is that people can get an overview of glucose levels. Method: the community participated in this activity on October 30 2022 around the Kadrie Oening Sports Center (GOR) in Samarinda City. The community is given the opportunity to follow the pressure of blood glucose levels and discussion about the glucose results obtained. Results: 99 participants consisting of 37 men and 62 women with an age range of 14-68 years. Participants were very enthusiastic in taking part in checking blood glucose levels using the POCT method and health dissemination as seen from the long wait of the participants and the implementation of the executors for the participants who took part in this activity. There were 8 (8.1%) participants with levels >200 mg/dl and 91 (91.9%) participants getting results <200 mg/dl. Then given health education related to blood glucose to the participants.